Sexual dimorphism in mud crabs: a tale of three sympatric Scylla species - Fazhan, Hanafiah; Waiho, Khor; Fujaya, Yushinta; Rukminasari, Nita; Ma, Hongyu; Ikhwanuddin, Mhd (PeerJ, 2021)
Sexual dimorphism is a common phenomenon in the animal kingdom. To test the consistency of sexual dimorphism patterns among sympatric species of the same genus, ten morphometric characteristics of mud crabs Scylla olivacea, S. tranquebarica and S. paramamosain were measured and compared using Discriminant Function Analysis (DFA). The descriptive analysis revealed that in all three species, body size dimensions and cheliped dimensions were significantly larger in males whereas the abdomen width was female-biased. Also, we described a morphological variation (carapace width, CW ≤ CW at spine 8, 8CW) that is unique to S. olivacea. Discriminant function analysis revealed that all nine morphometric characteristics were sexually dimorphic in S. olivacea, S. tranquebarica (except right cheliped’s merus length, ML) and S. paramamosain (except 8CW). The obtained discriminant functions based on the morphometric ratios (with CW as divisor) correctly classified 100% of adults of known sex of all three species. Further, based on the selected body traits, DFA was able to almost completely distinguish males (94%), but not females (74%), among the three Scylla species. This study highlights that congeneric species of portunids (e.g., Scylla spp.) show similar sexually dimorphic characteristics (body size and secondary sexual characteristics).
Keywords: Discriminant function; Morphometric; Morphology; Portunids; Sexual dimorphism; Scylla